Characterization of the prevalence of findings compatible with hydatidosis and fertility of hydatid cysts in cattle of a slaughterhouse in Curicó, Chile - Cruzat S., Antonio (2019)
The aim of this study was to determine the prevalence of findings compatible with hydatidosis and fertility of hydatid cysts in bovines of a slaughterhouse in Curicó, Chile. Lungs, livers, hearts, spleens and kidneys of 218 animals slaughtered in April 2017 were analyzed. The prevalence of findings compatible with hydatidosis was 12.4%, where 74.1% of affected animals presented lung cysts, 11.1% liver cysts and 14.8% of both types. Older animals concentrated the greatest number of findings. In samples of hydatid fluid from unilocular cysts a fertility of 6.25% was obtained. The prevalence of findings found was lower than the data described in national studies.